2009
DOI: 10.1016/j.ejor.2008.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Pure subgame-perfect equilibria in free transition games

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…The question arises whether we can also guarantee the existence of a positional Nash equilibrium in such games. Kuipers et al (2009) proved that this is not the case.…”
Section: Claim Prmentioning
confidence: 94%
“…The question arises whether we can also guarantee the existence of a positional Nash equilibrium in such games. Kuipers et al (2009) proved that this is not the case.…”
Section: Claim Prmentioning
confidence: 94%
“…It is shown in Kuipers et al [6] that this game has no stationary subgame-perfect 0-equilibrium, and similar arguments can be used to prove the non-existence of stationary subgame-perfect ε-equilibrium for small ε > 0.…”
Section: Stationary Strategiesmentioning
confidence: 99%
“…Indeed, this property implies that a finite number of deviations cannot be profitable either, and because the termination payoffs are nonnegative, no player can profit from deviating infinitely many times (that can only happen if play never terminates). By making use of this one-deviation principle, Kuipers et al [6] showed the existence of a pure subgame-perfect 0-equilibrium.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations